Cold plasma treatment to improve the safety and quality of pearl millet flour - Naraharasetti, Bindusri (My University, 2026)
Pearl millet flour (PMF) has a well-balanced protein content with fat, gluten-free, and low glycemic index, making it a substitute diet for diabetes and celiac disease. However, PMF spoils quickly due to enzymatic rancidity, thus limiting its shelf life, and anti-nutrient factors, such as tannins and phytic acid, also limit its usage. This study aims to inactivate quality deteriorating enzymes, viz. lipase, lipoxygenase, polyphenol polyphenol oxidase (PPO), and peroxidase (POD) by using cold plasma (5-25 kV; 2-10 min). Cold plasma treatment at 25 kV/8 min, led to 95.9 %, 99.2 %, 94.8 %, and 100 % inactivation of lipase, lipoxygenase, peroxidase, and PPO activity, respectively. Cold plasma-induced enzyme inactivation followed n th-order kinetics, such as 1.55, 1.35, 1.15, and 1.05 for lipase, peroxidase, lipoxygenase, and PPO, respectively. Steam treatment at 100 ℃/4 min inactivated lipase, lipoxygenase, peroxidase, and PPO by 97.9, 98.8, 97.6, and 100 %, respectively. The PMF showed 24.0 g/hg and 19.5 g/hg reduction in phytic acid and 77.7 g/hg and 16.9 g/hg reduction of tannin content at 25 kV/8 min of cold plasma treatment and steam treatment at 100 ℃/5 min, respectively. Color, particle size, and proximate composition remained unaffected; a reduction in secondary oxidation products and minor modifications in the secondary structure of the protein were observed in both treatments. Apart form the enzyme activity, PMF is contaminated with pathogenic species due to poor and unhygienic postharvest practices. This study aims to inactivate Salmonella spp, which cause foodborne illnesses, using the cold plasma treatment (20-28 kV/20-60 min). The effectiveness of the treatment is observed through different combinations of treatments, such as the contaminated pearl millet grains are treated with cold plasma treatment (A), grains tempered with plasma-activated water (B), and the contaminated pearl millet grain is milled to flour and treated with cold plasma treatment (C). Furthermore, with cold plasma treatment as all possible combinations of treatment such as A+B, B+C, A+C, and A+B+C. Cold plasma induced the highest microbial inactivation of 3.0 log cycle, with the combination treatment of A+B+C such as the cold plasma treatment of the grain, followed by tempering with plasma-activated water and cold plasma treatment of the flour at 28 kV/60 min. Through the individual treatment of the grains (A) and the combination of A + C achieved the highest reduction of 1.4 and 2.6 log CFU/g at 28 kV/60 min, respectively. A+B+C treatment condition shows a decrease in true, bulk, tapped density, an increase in the geometric mean diameter, and changes in the color profile observed due to the tempering of the grains. The third objective of the study is to optimizing its milling methods through pin mill and hammer mill and determination of dough rheological properties. Furthermore, develop bread using cold plasma-treated tempered and untempered pearl millet flour (PMF) using the optimal mixture design. Pin-milled PMF has a uniform particle distribution, and tempered pearl millet flour exhibited the highest yield, 93.5%. Varied proportions of the wheat flour (70-87 g), pearl millet flour (10-27 g), and shortening agent (3-6 g) were used to assess the bread hardness, crust color, and specific volume, as per D-optimal mixture design. A special cubic model was fitted to each response in both conditions. An optimized blend for the tempered flour composed of 85.5 g refined wheat flour,11.5 g PMF, and 3 g of shortening, having the hardness, total color change of crust, and specific volume 6.06 N, 5.47, and 2.82 mL.g⁻¹, respectively. Similarly, the untempered pearl millet flour has 75.6 g wheat flour, 18.3 g PMF, and 6 g of the shortening agent, comprising the hardness, total color change of crust, and specific volume 7.32 N, 6.60, and 3.04 mL.g⁻¹ respectively. Cold plasma treatment 25 kV/8 min enhances the overall functional properties and texture attributes of the bread.
Keywords: Lipase; Lipoxygenase; Peroxidase; Polyphenol oxidase; Phytates; Pearl millet; Salmonella; Cold plasma treatment; Plasma-activated waters